How Distortive Are Turnover Taxes? Evidence from Replacing Turnover Tax with VAT - Jing Xing; Katarzyna Anna Bilicka; Xipei Hou (Center for Economic Studies and ifo Institute (CESifo), 2022)
In this paper, we investigate distortions created by turnover taxes. As a natural experiment, we explore a reform that replaced turnover taxes with value-added taxes for some service industries in China, while the taxation of manufacturing industries remained unchanged. The reform increased sales, R&D investment, and employment for affected service firms, which is primarily driven by outsourcing from downstream manufacturing _rms. We document that smaller and less innovative manufacturing firms outsource more, and reallocation increases the quality of innovation for affected service firms. Our study provides new evidence on the negative impact of turnover taxes imposed on business inputs.
Keywords: H25; H26; O32; D25; 330; turnover tax; value-added tax; outsourcing; R&D investment